Design and fabrication of home drain cover - Muhammad Ruzilan, Rusli (2012)
My final year project is about to design and fabricate a home drain cover.Home drain cover is important equipment because it protects and prevents someone from fall into the drain. Furthermore, the drain cover can help us to cross the drain easily. However, former home drain covers existing in the market do not have security features that can prevent any pets from come in through the front yard of the drain into our home area. It also can easily break because it cannot stand a heavy mass object for a long time. However, the reason we need a new concept for a home drain cover. The main features of home drain cover can prevent pets coming through the front yard of the drain to our home area. This idea emerged because of the lack of modification is available on the product time. The idea to form home drain cover is based on the students own creativity. The selection of materials suitable for the formation is based on the weight of a suitable material, durable and ability to withstand load. Material proposed for the formation of home drain cover is mild steel. Several processes are necessary and when they form a home drain cover contained in this report.